Seismic Signature of Transition Zone (Wolf Ramp) in Shale Deposits with Application of Frequency Analysis - Anna Kwietniak; Tomasz Maćkowski; Kamil Cichostępski (Geofluids)
The concept of a transition zone, known as Wolf ramp, was incorporated into the seismic interpretation of a 3D seismic survey situated within the Baltic Basin (Northern Poland). Within the survey area, there exists one formation, the Pasłęk Formation, (Lower Silurian—Llandovery), that exhibits a linear change of velocity. This characteristic—linear change of velocity—causes a reflection coefficient (i.e., seismic amplitude) produced at such a boundary to be frequency dependent. The Pasłęk Formation was considered to be a potential shale gas reservoir and it was necessary to determine its structural position and thickness. The formation is challenging for robust seismic interpretation on the migrated seismic section—it does not manifest a stable reflection coefficient, and the amplitude contrast associated with the borders of the formation is low. There is no impedance contrast that would produce a reflection of high amplitude at the top or base of the formation which excludes determination of the formation thickness, hence the estimation of reservoir volume. Within a 3D dataset, there exists only one well with complete logs that were used for the analysis. The Pasłęk Formation is a flat-lying layer that continues itself far beyond the 3D survey. It is present in wells in the vicinity of the study area. These wells lay within other 3D or 2D datasets, but the quality of the seismic is poor, and similar seismic analysis is not possible. Nevertheless, these wells were incorporated in the research to reason about the possible link between the existence of transition zone and mineral content. The method used for recognition of transition zone is spectral decomposition and spectral analyses. The integrated studies enabled us to find a link between the Wolf ramp and mudstone-claystone interval of the Silurian age and give a new example of a transition zone which is present in shale plays. The transition zone concept might be applied for shale plays identification and analysis.